Model Pembelajaran Kooperatif Tipe Make A Match Pada Topik Penamaan Senyawa Dan Persamaan Reaksi Di Kelas X SMA Negeri 1 Dampelas - Hardianti, Titi; Pursitasari, Indarini Dwi; Tangkas, I Made (Jurnal Akademika Kimia, 2014)
The learning method applied on chemistry study nowadays is still one-way; students act as listeners and are not active on learning processes in the classroom. The goal to be achieved on this research was to determine the effect of cooperative leraning model make a match type on compounds and chemical equations naming topic towards the students’ learning outcome and to their critical thinking skill of X grade students of SMA Negeri 1 Dampelas consisting of 6 classes. 2 classes were taken as samples by purposive sampling; 28 students of class XE as control class and 28 students of class XF as the experimental class. The research instruments used were tests and observation sheet. Descriptive and inferential statistics analysis methods were used asthe data analysis technique. Statistics analysis of right side t-test was used for testing the research data. The average score of learning outcome achieved as the research result were 78.96 of experimental class and 60.92 of control class and the average score of critical thinking skill were 74.75 for the experimental class and 65.75 for the control class. The research result showed that the use of cooperative learning model make a match type on compounds and chemical equation naming topic made the students’ learning outcome and crictical thinking skill better.